Gunsmoke movie collection [videorecording (DVD)] / Return to Dodge ; The last Apache ; To the last man. - Arness, James, 1923-2011; Learned, Michael; Kiley, Richard; Hough, Stan; Wallace, Earl W.; Correll, Charles; Hingle, Pat; Woodward, Morgan, 1925-2019; Swor, Ken; Jameson, Jerry; Holliman, Earl, 1928-; Blake, Amanda; et al. (CBS Broadcasting, Inc., 2018)
Return to Dodge-Ex-Marshall Matt Dillion is stabbed in a fight with a band of thieves. When word reached Miss Kitty, she returns to be by his side. However, danger strikes again as an old enemy is released from prison and to vows to settle the score.